The Role of Islamic Boarding Schools in Fostering the Independence of New Santri at the Nurul Iman Islamic Boarding School in Bandung - Nur Ainiyah; Dadang Hidayat; Fauzaan Allaamsyah Harun; Linda Nur Kirani; Siti Pathonah Zahroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Independence is a character that every student must have so that they are mentally strong in adapting to Islamic boarding schools and are also able to solve the various problems they face. The theory used in this research is. Santri, Islamic Boarding Schools, Typology of Islamic Boarding Schools and Independence. In this research, researchers used a qualitative method using a case study approach. Data were collected through interviews, observation and documentation. This research aims to find out the condition of the Nurul Iman Islamic Boarding School in Bandung, what role the Islamic Boarding School plays in increasing the independence of its students at the Nurul Iman Islamic Boarding School and also to find out what factors are obstacles in increasing the independence of students at the Nurul Iman Islamic Boarding School in Bandung. The research population is Nurul Iman Islamic boarding school students. The research results show that Islamic boarding schools have programs to build independence which is very important in increasing the independence of new students, in this case it can be seen from the difference between the first time you enter an Islamic boarding school and after living in an Islamic boarding school for a long time. The santri's attitude of independence is demonstrated by always carrying out their obligations and practicing in daily life within the Islamic boarding school and outside the Islamic boarding school, the santri can be disciplined and on time, and not depend on other people.